Munhålestatus hos arbetande hästar - Tell, Anna (SLU/Dept. of Large Animal Clinical Sciences, 2004)
Seventy-two working horses (they had been ridden with bit and bridle within the last two weeks) were examined in the oral cavity. Findings and status were noted. The horses were randomly chosen among individuals without clinical symptoms from the mouth and gastrointestinal system.